2003
DOI: 10.1097/01.inf.0000078159.53132.40
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bloodstream infections in pediatric patients in United States hospitals: epidemiology, clinical features and susceptibilities

Abstract: Nosocomial BSI occurred predominantly in very young and/or critically ill children. Gram-positive pathogens predominated across all ages, and increasing antimicrobial resistance was observed in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
199
6
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(221 citation statements)
references
References 16 publications
10
199
6
6
Order By: Relevance
“…This finding was in line with the report from the US [54], while Gram-negative pathogens predominated in the other two studies [53,245]. Neither methicillin resistance in S. aureus isolates nor vancomycin resistance in E. faecium isolates was detected during the study.…”
Section: Microbiological Aspectssupporting
confidence: 81%
See 3 more Smart Citations
“…This finding was in line with the report from the US [54], while Gram-negative pathogens predominated in the other two studies [53,245]. Neither methicillin resistance in S. aureus isolates nor vancomycin resistance in E. faecium isolates was detected during the study.…”
Section: Microbiological Aspectssupporting
confidence: 81%
“…Neither methicillin resistance in S. aureus isolates nor vancomycin resistance in E. faecium isolates was detected during the study. The finding differed from the corresponding rates of the US study (16% and 11%, respectively) [54] …”
Section: Microbiological Aspectscontrasting
confidence: 56%
See 2 more Smart Citations
“…Enterobacteriaceae found in livestock and on retail meat include the opportunistic pathogens Escherichia coli and Klebsiella (Davis and Price, 2016;Davis et al, 2015;Nordstrom et al, 2013), which are the most common causes of urinary tract infections and among the most common causes of bloodstream infections in patients (Davis and Price, 2016;Diekema et al, 2003;Laupland and Church, 2014;Laupland et al, 2007;Russo and Johnson, 2003;Wisplinghoff et al, 2004). Staphylococcus aureus, the most common cause of skin infections and second most common cause of bloodstream infections in patients (Brook and Frazier, 1995;Carratala et al, 2003;Diekema et al, 2001;Sigurdsson and Gudmundsson, 1989;Wisplinghoff et al, 2003a;Wisplinghoff et al, 2003b;Wisplinghoff et al, 2004), is also found on the skin of livestock and on retail meat (Smith, 2015;Smith and Wardyn, 2015). These organisms move easily between farm animals and humans and also from humans to other humans in the community and in health care settings.…”
Section: The Current State Of Antibiotic Resistancementioning
confidence: 99%